2006
DOI: 10.2351/1.2227016
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-fracture of prescored alumina ceramics using simultaneous CO2 lasers

Abstract: While brittle materials such as ceramics will clearly be at the forefront of improved energy efficiency, manufacturing problems related to shaping have proven to be troublesome. Fortunately, the usage of laser machining to shape structural ceramics is increasingly gaining acceptance as an alternative to traditional grinding and cutting methods. Despite the great promise of lasers for a variety of cutting and drilling procedures, premature fractures, poor surface quality, microscale damage, and prohibitively lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…It is inefficient to use furnace to heat the glass. A feasible method to reduce thermal gradients is preheating glass by CO2 laser before machining, that is the process of manufacturing glass with dual CO2 laser beams is briefly illustrated [13,14]. The preheating laser beam preheats glass to a proper temperature, which can reduce the thermal stress in glass when machined by machining laser beam.…”
Section: Experimentation Verificationmentioning
confidence: 99%
“…It is inefficient to use furnace to heat the glass. A feasible method to reduce thermal gradients is preheating glass by CO2 laser before machining, that is the process of manufacturing glass with dual CO2 laser beams is briefly illustrated [13,14]. The preheating laser beam preheats glass to a proper temperature, which can reduce the thermal stress in glass when machined by machining laser beam.…”
Section: Experimentation Verificationmentioning
confidence: 99%
“…One is the controlled fracture method and the other is melting means. The former has attracted more attention and lots of research has been reported in literatures [7][8][9][10][11][12][13][14][15][16]. In contrast, very few studies have been made in detail to investigate cutting glass with the melting method except by Chui [17], due to the low thermal conductivity and the brittleness of the glass material.…”
Section: Introductionmentioning
confidence: 98%
“…With the development of laser technology, many studies have been carried out on cutting glass with lasers [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Li et al [3] put forward a mathematical model to explain the heat transfer of glass heated by a laser beam.…”
Section: Introductionmentioning
confidence: 99%
“…They used a fixed grid algorithm to model the ablation process and the model developed was integrated with a probabilistic fracture model to assess the failure probability during the laser cutting process. Brugan et al [9] introduced a new method to control fractures for the fast laser machining of lamina plates. They accommodated the simultaneous scoring technique to enhance the thermal stresses for driving a propagating crack along a pre-ordained path using simultaneous CO 2 laser.…”
Section: Introductionmentioning
confidence: 99%